Effective management of high failure rates in grade nine classes : a case study of the Mamabolo Circuit - Ramoshai, Mankaleme Emily (My University, 2016)
This study is an investigation of effective management of high failure rates in grade nine classes in selected schools of the Mamabolo circuit. The study was prompted by several factors such as repetition rate, overcrowding and over-aged learners experienced in grade nine classes. The problem statement provides the foundation within which the aim and objectives are described. The causal factors of grade nine failure rates and how the management of schools was affected were not overlooked. The main targets were the School Management Teams of selected schools in the Mamabolo circuit. A qualitative research method was used. Various methods of data collection were used such as face-to-face interview, observation and document analysis whereby the summary of learner performance, collected from the circuit office, was analysed. Key findings of this research suggest that the School Management Teams are faced with great challenges that emanate from high failure rates in grade nine classes. The majority of the schools in the Mamabolo circuit are characterised by very low school enrolment which affects the post establishment and results in management overload. Congestion in the classrooms is experienced in grade nine classes (see figure 4.5). Most of the School Management Teams consist of one principal and one HOD, while other members are post level one educators who are senior educators (see table 3.1). This situation, in some instances leads to reluctance in performing management duties as compared to the schools where the School Management Teams are constituted by appointed principal, deputy principal/s and HODs only. Grade nine classes are not effectively managed due to various challenges such as overcrowding, lack of furniture, shortage of Learner Teacher Support Material, over-aged learners, low morale, discipline problems, poor involvement of parents, teenage pregnancies and drop-outs. Furthermore, the study revealed that very few School Management Teams seem to acknowledge that they also contribute to the failure rate in grade nine. This was clearly indicated when the School Management Teams were responding to the question on the causes of poor academic performance in grade nine classes. Learners, parents, educators, some departmental policies and the Department of Education itself were mentioned as contributing factors to poor performance. The following conclusions were drawn from the study findings: There are serious challenges facing the School Management Teams in the Mamabolo circuit, which are emanating from high failure rates in grade nine classes. The School Management Teams find it difficult to effectively manage high failure rates. High failure rates have a negative impact on the management of schools and affect the functionality of the school as an institution of learning. Finally, although the School Management Teams in the Mamabolo circuit fail to effectively manage high failure rates in grade nine, this investigation indicates that they are very aware of their responsibilities as members of the School Management Teams. In order to improve the effective management of the School Management Teams, to eliminate the challenges experienced and to increase learner attainment in grade nine classes, the following recommendations should be considered: skills development workshops, planning, implementation and monitoring of curriculum activities, provision of human and physical resources and parental involvement.
Thesis (MPA.) -- University of Limpopo, 2016
Keywords: Management of high failure rate; Grade nine classes; Mamabolo Circuit; Low-performing schools; School failure